Comparative Studies on Marek’s Disease Virus and Herpesvirus of Turkey DNAs - Hirai, Kanji; Ikuta, Kazuyoshi; Kato, Shiro (Journal of General Virology, 1979)
SUMMARY DNA of Marek’s disease virus (MDV) was compared to that of herpes virus of turkey (HVT). Centrifugation of the two virus DNAs in neutral glycerol and CsCl density gradients showed that the MDV genome was slightly larger than that of HVT and that the buoyant density (1.705 g/ml) of MDV DNA in CsCl gradients was slightly lower than that (1.707 g/ml) of HVT DNA. MDV and HVT DNAs were digested with either EcoRI or HindIII restriction endonuclease and analysed by 0.5% agarose gel electrophoresis. The cleavage patterns of HindIII or EcoRI DNA digests of two strains of these two viruses showed general similarities between the strains, but not between MDV and HVT. However, a few fragments of EcoRI or HindIII digests of MDV DNA co-migrated with those of HVT DNA. DNA-DNA reassociation kinetics and DNA-RNA hybridization between these two viruses indicated that MDV and HVT DNAs share detectable homology, although it is less than 5%. The DNA of a HVT variant, which has lost the ability to protect chickens from Marek’s disease, appeared similar to DNA of the vaccine strain in size and buoyant density and in its restriction endonuclease cleavage pattern.